Sociodemographic characteristics of patients with chronic headache - Sampaio, Patrick Giordanni Gomes; Maracajá, Hiago Diniz; Figueiredo, Sara Raquel Nóbrega; Figueiredo, Virgínia Gabriela Nóbrega; Temoteo, Túlio Carneiro Monteiro; Melo, Nátalia Meg Adijuto de (Headache Medicine, 2020)
Introduction: Headache is an entity characterized by a painful process in the cephalic segment and may originate from cranial or facial structures, being considered a common medical complaint. The chronification process of the pain can present a decrease in quality, the functional capacity and the patient’s and labor environment, and also as well as affect their interpersonal relationships, since the chronic cephalalgic process can lead the patient to moments of social isolation, mood swings, depression. Methods: The research was conducted through a retrospective cross-sectional study, performing the analysis of medical records of patients seen at the Unifacisa’s outpatient neurology School Clinic complaining of chronic headache, from February 1st to August 31, 2019. Results: With the analysis of the medical records, 684 attendances were obtained, where 30 of the patients treated had the diagnosis of chronic headache, 29 women and 01 man. These patients received the following diagnoses: 18 (60%) patients with chronic migraine without aura, 4 (13.3%) patients with chronic migraine with aura, 12 (40%) patients with chronic daily medication overuse headache, 9 (30%) patients with chronic tensiontype headache (CTTH), 1 (3.3%) patient with basilar migraine, 2 (6.6%) patients with secondary headache. Conclusion: Although a small number of chronic headache patients were obtained, yet we realize that it is the migraine that leads to a greater demand for specialized medical care. In addition, as expected due to the latest research, a significant number of patients with headache due to excessive use of common painkillers.